Land, property relations, and urban planning: New histories from colonial India - Sengupta, Kaustubh Mani (History compass, 2022)
This article looks at the recent scholarship on urban property in colonial India. Histories of cities of British India have been dominated by issues of racial segregation, discourse of planning, ways of social control as well as negotiation and resistance of the indigenous population in fashioning the urban space. The new scholarship brings in economic considerations of the state and the private actors squarely to the foreground to argue that land and property was at the heart of urban governance. Putting forward a materialist interpretation of the production of colonial urban space, these histories provide a lens to view the complex and complicated processes through which land turned into commodity. The article discusses three major issues relating to urban property regime as have been argued variously in these writings: first, it looks at the very constitution of the meaning of property and rights to property; second, it studies the various meanings of ‘value’ of a land; and lastly, it considers the question of workings of the property market in relation to housing and rent. The readings suggest that specific political, socio-economic, and ecological context of each city shaped much of the deliberations and responses to the emergence and consolidation of a property regime.